MAKNA TRADISI NGLARUNG AYAM PADA PERKAWINAN DI MASYARAKAT DESA KALIJAMBE, KECAMATAN BRINGIN, KABUPATEN SEMARANG - Dini Agustin; Kuncoro Bayu Prasetyo (Universitas Hamzanwadi, 2024)
One of the marriage traditions still being preserved today is the tradition of Nglarung Ayam by the people of Kalijambe Village. Nglarung is a tradition in Javanese society to throw offerings in the sea or river. The aims of this research are as follows: 1) to find out the implementation of the Nglarung Ayam tradition at weddings in the Kalijambe Village community, 2) to analyze the meaning behind the Nglarung Ayam tradition carried out by the Kalijambe Village community. The research method used is a descriptive qualitative research method with data collection techniques in the form of observation and interviews. The research results show that the tradition of Nglarung Ayam is carried out when residents of Kalijambe Village get married and get a partner from outside the village who are separated by a river and cross a bridge. Nglarung Ayam is done by releasing free-range chickens on the bridge that the bridal party crosses to their partner's house. Nglarung Ayam has two meanings. The incidental meaning applies during the journey to the in-law's house as a reinforcement to protect the bridal party from danger on the way to the couple's house. The second is the meaning of continuity, namely, the hope of ensuring future harmony and happiness for the bridal couple.